Comparison of intravenous ketamine hydrochloride plus dexmedetomidine hydrochloride and ketamine hydrochloride plus midazolam hydrochloride in procedural sedation for short surgical procedures: A prospective randomized double-blind study - Dilip Kothari; Seethal Ann Sunny; Anjali Bansal (Asian Journal of Medical Sciences, 2023)
Background: The growing popularity of ambulatory anesthesia has led to the development of newer drug regimens and combinations. We decided to compare the effects of ketamine plus dexmedetomidine versus ketamine plus midazolam in procedural sedation. Aims and Objectives: The present study aimed to compare the effects of ketamine plus dexmedetomidine versus ketamine plus midazolam on the adequacy of anesthesia, level of sedation and analgesia, hemodynamic and respiratory parameters, recovery time, and post-operative side effects in short surgical procedures. Materials and Methods: Hundred adult patients were randomized into two groups: Group KD: A bolus dose of Dexmedetomidine 1 mcg/kg in 100 ml NS over 10 min and Group KM: A bolus dose of Midazolam 0.05 mg/kg in 100 ml NS over 10 min. Both groups received bolus dose of Ketamine 1 mg/kg at the start of the procedure. Level of sedation, adequacy of anesthetic technique, hemodynamic parameters, time for rescue analgesia, post-operative recovery time, and complications was measured. Results: In Group KD 7 (14%) patients and in Group KM 13 (26%) patients had inadequate anesthesia. A significant reduction in pulse rate (P<0.001) was observed in Group KD as compared to Group KM. MAP between the two study groups showed a statistically significant reduction in Group KD as compared to Group KM (P<0.05). Time for first rescue analgesia was delayed in Group KD (70.20±14.35) compared to that of Group KM (49±4.73) (P=0.000). Four (8%) patients in Group KD and 11 (22%) patients in Group KM had post-operative nausea and vomiting. Conclusion: Dexmedetomidine-ketamine combination is a good and safe alternative agent for procedural sedation in patients undergoing short surgical procedures.